Triangulation study of needs assessment of people with severe mental illness in "follow‐up" day hospital settings - Tanja Torkar; Vesna Homar; Vesna Švab (Wiley, 2023)
Abstract Aim The aim of research was to assess the needs of patients with severe mental illness (SMI) attending follow‐up day hospital (DH) programmes from the patients', relatives' and experts' perspective. Design This triangulation research relies on three sources of information and two techniques of data collection. Methods Qualitative research was conducted comprising semi‐structured interviews (n = 15) and focus groups (n = 4) in three sequential rounds, triangulating patients', relatives' and experts' views. A content analysis was carried out. Results Study reveals a diverse spectrum of needs of SMI patients in follow‐up DH programmes. The analysis yielded six themes: optimal daily functioning, work and educational activities, social network inclusion, continuous treatment, support and guidance, long‐term care. DH programmes should assess the needs of patients with SMI and be adapted according to the findings. In addition to clinical treatment, requirements for continuous treatment, psychological and social needs, therapeutic relationship in less‐restrictive settings should be considered.